2017
DOI: 10.1038/nchembio.2297
|View full text |Cite
|
Sign up to set email alerts
|

Selective in vivo metabolic cell-labeling-mediated cancer targeting

Abstract: Distinguishing cancer cells from normal cells through surface receptors is vital for cancer diagnosis and targeted therapy. Metabolic glycoengineering of unnatural sugars provides a powerful tool to manually introduce chemical receptors onto the cell surface; however, cancer-selective labeling still remains a great challenge. Herein we report the design of sugars that can selectively label cancer cells both in vitro and in vivo. Specifically, we inhibit the cell-labeling activity of tetraacetyl-N-azidoacetylma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
259
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(271 citation statements)
references
References 51 publications
4
259
0
1
Order By: Relevance
“…[6] As the cell surface displays the azide groups, a molecule bearing dibenzocyclooctyne (DBCO) would react with the membrane glycoproteins via copper-free click chemistry. [11,12] The results (Figure S1) showed that the surface of the Ac 4 ManNAz-fed cells could display DI after treated with DI-DBCO. While we applied Ac 4 ManNAz for DI display, it is possible to use other methods to realize the same purpose.…”
mentioning
confidence: 99%
“…[6] As the cell surface displays the azide groups, a molecule bearing dibenzocyclooctyne (DBCO) would react with the membrane glycoproteins via copper-free click chemistry. [11,12] The results (Figure S1) showed that the surface of the Ac 4 ManNAz-fed cells could display DI after treated with DI-DBCO. While we applied Ac 4 ManNAz for DI display, it is possible to use other methods to realize the same purpose.…”
mentioning
confidence: 99%
“…[40] Then, MDT-activated TGF-β1 was immobilized onto the azidefunctionalized antigen-presenting cell (APC) surface through a mild biorthogonal reaction, providing ease in translating this strategy to innumerable biomaterial platforms to modulate the transplant environment. [42] This so-called Adv. [41] Nanoparticles with a hydrazine moiety could be conjugated to the aldehyde groups to form stable secondary amine linkages through the Mannich reaction ( Figure 2F).…”
Section: Chemical Engineering Of the Cell Membranementioning
confidence: 99%
“…[44] Then, the magnetic nanoclusters (MNCs) were cloaked with engineered membranederived vesicles to form artificial APCs, leading to more efficient T-cell expansion and increased cytotoxicity. [42] Copyright 2017, Nature Publishing Group. Reproduced with permission.…”
Section: Chemical Engineering Of the Cell Membranementioning
confidence: 99%
“…Subsequent click chemistry allows the delivery of alkyne labeled dibenzocyclooctyne‐doxorubicin to the cancer cells. Such a strategy enabled targeted therapy and substantially reduced toxicity on noncancerous cells . Therefore, metabolic engineering approach offers unprecedented opportunities to study the biological functions of cell surface glycans or develop novel therapeutics for disease treatment.…”
Section: Indirect Chemical Modification Of Cell Surface Using Unnaturmentioning
confidence: 99%